The Application of Fuzzy VIKOR for the Design Scheme Selection in Lean Management. (10th September 2018) - Jing, Shuwei; Tang, Yao; Yan, Junai
Abstract : Given that using the same evaluation criteria in group decision making (GDM) may cause solution bias, this research proposes the decision making model using improved fuzzy VIKOR and takes the lean management design scheme selection process in a real estate company as an example to study the way of decision making. Research results are as follows: (1) improved fuzzy VIKOR allows different decision makers to evaluate all schemes with respect to different evaluation criteria systems and, based on this, this research proposes a decision making model which can effectively avoid making decision using the same criteria system; (2) this decision making model is very scientific, as it is not sensitive to the coefficient of selection mechanism, the weight of decision maker, and the weight of evaluation criterion, so the decision results are very stable; (3) the decision making model proposed in this research can effectively obtain the optimal result and avoid suboptimal solution.